2004
DOI: 10.1136/bjo.2003.027573
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hyaluronate (hyaluronic acid) promotes migration of human corneal epithelial cells in vitro

Abstract: Purpose: Sodium hyaluronate (hyaluronic acid) is known to promote corneal epithelial wound healing in vivo and in vitro, in animal experiments. Sodium hyaluronate is the ligand for CD44, a cell surface adhesion molecule which has been found on normal human corneal epithelial cells. The purpose of this study was to investigate the effect of sodium hyaluronate on human corneal epithelial cell migration, proliferation, and CD44 receptor expression. Methods: Human corneal epithelial cell cultures were established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
1
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(165 citation statements)
references
References 43 publications
5
143
1
7
Order By: Relevance
“…29 HA has been shown to reduce pathologic changes in articular fluid. 29 Gomes et al 30 reported HA promoted migration but not proliferation on human corneal epithelial cell in vitro. They suggested the beneficial effect of HA in corneal wound healing was likely to be related to rapid migration of cells.…”
Section: Discussionmentioning
confidence: 99%
“…29 HA has been shown to reduce pathologic changes in articular fluid. 29 Gomes et al 30 reported HA promoted migration but not proliferation on human corneal epithelial cell in vitro. They suggested the beneficial effect of HA in corneal wound healing was likely to be related to rapid migration of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Supõe-se que a interação do AH com a superfície corneal provocaria o aumento do número de receptores CD44, uma glicoproteína transmembrana envolvida na re-epitelização corneal (18) . Gomes et al, compararam o crescimento de células epiteliais humanas em três meios de cultura diferentes, um deles enriquecido com NaAH 0,6%.…”
Section: Figura 1 -Estrutura Do áCido Hialurônicounclassified
“…Gomes et al, compararam o crescimento de células epiteliais humanas em três meios de cultura diferentes, um deles enriquecido com NaAH 0,6%. Houve maior aumento da migração celular no meio enriquecido com NaAH, fazendo-os concluir que NaAH exerce maior efeito na migração das células do epitélio corneal humano quando comparado com os outros meios de cultura estudados (18) .…”
Section: Figura 1 -Estrutura Do áCido Hialurônicounclassified
“…Para que haja transparência da córnea é preciso que seu epitélio e filme lacrimal estejam íntegros (2,3) . O tempo de cicatri zação da córnea, na presença de lesão epitelial, pode influenciar em sua transparência e na qualidade óptica resultante (4) .…”
unclassified